To what extent employee stock ownership plan impact the stock price of Chinese listed companies - Shen, Jie (2018)
With the issuance of the guidance on employee stock ownership plan by China securities regulatory commission in 2014, Chinese employee stock ownership plan is gradually on the right track and more and more companies begin to implement ESOP. Taking Shanghai and Shenzhen listed companies from 2016 to 2017 as sample, this paper discusses the overall impact of ESOP on the stock price of listed companies through event study. It could be found that the implementation of ESOP can significantly improve the stock price of listed companies in the short term. Moreover, in order to further study how the implementation of ESOP affects the stock price of listed companies, this paper explore the impact of the company nature and ESOP content on the stock price of companies.It could be found that the effect of ESOP in high-tech industry is not as good as that of other industries. Companies that use employee self-financing to obtain funds are more conducive to the rise of the stock price of listed companies. Furthermore, the effect of implementing ESOP by a company with large fundraising is better than a company with a small fundraising scale in a short period of time. In addition, the size of the company implementing the employee stock ownership plan has little effect on the stock price